Financial statement analysis - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2022)
The case describes the Financial Statement Analysis interactive learning object. It is aimed at students taking the COR1307 Accounting for Entrepreneurs course in particular, as well as other basic financial accounting courses (ACCT101 and ACCT111 – Financial Accounting) and basic finance courses. The course is designed to provide a broad base coverage of issues related to accounting, such as basic accounting concepts and their applications to businesses, capital-raising, short-term and long-term financial planning, managerial accounting principles and concepts, management planning and control, as well as taxation that are relevant to future business owners and entrepreneurs. Business owners and entrepreneurs need the general foundation to help plan and control business operations and finance as well as discussing and negotiating with other stakeholders of the business. The key learning objectives of the Financial Statement Analysis learning object include: explain the nature and purpose of conducting financial statement analysis, perform horizontal and trend analysis, conduct vertical analysis, carry out ratio analysis, and identify the warning signals or “red flags” when performing financial statement analysis.